The Effect of Food Security on National Resilience - Afifah Hanaa Nur Alaf; Kasih Prihantoro; Suprapto Suprapto (Pusat Riset dan Inovasi Nasional, 2026)
National resilience serves as an important foundation for security as it allows a nation to both safeguard and maintain its core functions during disruptions. Many factors affect a nations resilience but food security stands as a critical factor that is often overlooked. This element directly impacts public welfare, socio-economic stability, and effective governance. Issues in this sector leads to cascading impacts that undermine societal cohesion, weaken government capacity, and ultimately reduce national resilience. This study examines the relationship between food security and national resilience in Indonesia. Using a qualitative approach through a literature review, the research analyses academic works, institutional reports, and policy documents to explore how food security interacts with national resilience frameworks. The findings show that sustainable and stable food systems strengthen adaptability, social stability, and national unity, whereas disruptions in food supply or access may trigger social unrest, economic instability, and governance challenges. The study concludes that integrating food security into Indonesia’s defence and security strategies is essential for strengthening national resilience amid emerging and complex global threats.